Effects of Plyometric Jump Training on Balance Performance in Healthy Participants: A Systematic Review With Meta-Analysis - Ramachandran, Akhilesh Kumar; Singh, Utkarsh; Ramirez-Campillo, Rodrigo; Clemente, Filipe Manuel; Afonso, José; Granacher, Urs (Frontiers in Physiology, 2021)
Background: Postural balance represents a fundamental movement skill for the successful performance of everyday and sport-related activities. There is ample evidence on the effectiveness of balance training on balance performance in athletic and non-athletic population. However, less is known on potential transfer effects of other training types, such as plyometric jump training (PJT) on measures of balance. Given that PJT is a highly dynamic exercise mode with various forms of jump-landing tasks, high levels of postural control are needed to successfully perform PJT exercises. Accordingly, PJT has the potential to not only improve measures of muscle strength and power but also balance. Objective: To systematically review and synthetize evidence from randomized and non-randomized controlled trials regarding the effects of PJT on measures of balance in apparently healthy participants. Methods: Systematic literature searches were performed in the electronic databases PubMed, Web of Science, and SCOPUS. A PICOS approach was applied to define inclusion criteria, (i) apparently healthy participants, with no restrictions on their fitness level, sex, or age, (ii) a PJT program, (iii) active controls (any sport-related activity) or specific active controls (a specific exercise type such as balance training), (iv) assessment of dynamic, static balance pre- and post-PJT, (v) randomized controlled trials and controlled trials. The methodological quality of studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. This meta-analysis was computed using the inverse variance random-effects model. The significance level was set at p <0.05. Results: The initial search retrieved 8,251 plus 23 records identified through other sources. Forty-two articles met our inclusion criteria for qualitative and 38 for quantitative analysis (1,806 participants [990 males, 816 females], age range 9–63 years). PJT interventions lasted between 4 and 36 weeks. The median PEDro score was 6 and no study had low methodological quality (≤3). The analysis revealed significant small effects of PJT on overall (dynamic and static) balance (ES = 0.46; 95% CI = 0.32–0.61; p < 0.001), dynamic (e.g., Y-balance test) balance (ES = 0.50; 95% CI = 0.30–0.71; p < 0.001), and static (e.g., flamingo balance test) balance (ES = 0.49; 95% CI = 0.31–0.67; p < 0.001). The moderator analyses revealed that sex and/or age did not moderate balance performance outcomes. When PJT was compared to specific active controls (i.e., participants undergoing balance training, whole body vibration training, resistance training), both PJT and alternative training methods showed similar effects on overall (dynamic and static) balance (p = 0.534). Specifically, when PJT was compared to balance training, both training types showed similar effects on overall (dynamic and static) balance (p = 0.514). Conclusion: Compared to active controls, PJT showed small effects on overall balance, dynamic and static balance. Additionally, PJT produced similar balance improvements compared to other training types (i.e., balance training). Although PJT is widely used in athletic and recreational sport settings to improve athletes' physical fitness (e.g., jumping; sprinting), our systematic review with meta-analysis is novel in as much as it indicates that PJT also improves balance performance. The observed PJT-related balance enhancements were irrespective of sex and participants' age. Therefore, PJT appears to be an adequate training regime to improve balance in both, athletic and recreational settings.